2006
DOI: 10.1097/01.prs.0000234612.20611.5a
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Poly-L-Lactic Acid (Sculptra): Technical Considerations in Soft-Tissue Contouring

Abstract: The authors therefore have opted for a more conservative approach in their treatment recommendations. Higher volume dilution (8 to 12 cc), fewer vials used at each session, injections placed in the subcutaneous plane without any product being placed in the dermis, adequate time between injection sessions (at least 6 weeks), and postinjection patient massage should decrease the risks and avoid the potential complications associated with poly-L-lactic acid soft-tissue augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
137
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(143 citation statements)
references
References 9 publications
0
137
0
6
Order By: Relevance
“…As physicians have become more familiar with injectable PLLA, it has become apparent that the reconstitution and administration of this injectable device (injectable filler), including correct placement of the material, are important parameters in ensuring optimal outcomes and minimizing adverse events. 14 This article aims to review the literature regarding the use of injectable PLLA in the European Union and United States for both HIV-associated facial lipoatrophy and facial cosmetic augmentation, in addition to describing how previous experience with PLLA can help improve future treatment outcomes. The information reported in this article is as detailed within the reviewed references and, as such, may not reflect manufacturer recommendations for the preparation and administration of injectable PLLA.…”
mentioning
confidence: 99%
“…As physicians have become more familiar with injectable PLLA, it has become apparent that the reconstitution and administration of this injectable device (injectable filler), including correct placement of the material, are important parameters in ensuring optimal outcomes and minimizing adverse events. 14 This article aims to review the literature regarding the use of injectable PLLA in the European Union and United States for both HIV-associated facial lipoatrophy and facial cosmetic augmentation, in addition to describing how previous experience with PLLA can help improve future treatment outcomes. The information reported in this article is as detailed within the reviewed references and, as such, may not reflect manufacturer recommendations for the preparation and administration of injectable PLLA.…”
mentioning
confidence: 99%
“…It has been also suggested that toxic substances already present in the body are attracted to the site of implant and initiate a granulomatous reaction [19]. This theory may explain why granulomas may develop throughout the bed of implantation rather than being limited to a few foci [18].…”
Section: Discussionmentioning
confidence: 98%
“…Because each patient responds differently to treatment with injectable PLLA, it is important to allow sufficient time between treatments to avoid overcorrection of the original deficit. Overcorrection of the injected area may produce an unwanted visual effect, and may contribute to the formation of subcutaneous nodules (31,53,54). It should be emphasized that the effects of treatment with injectable PLLA are gradual and long lasting (55).…”
Section: Discussionmentioning
confidence: 99%